Synthesis, Characterization and Biological Evaluation of New 3,5-Disubstituted-Pyrazoline Derivatives as Potential Anti-Mycobacterium tuberculosis H37Ra Compounds - Wong, Kok Tong (Molecules, 2021)
A total of fourteen pyrazoline derivatives were synthesized through cyclo-condensation reactions by chalcone derivatives with different types of semicarbazide. These compounds were characterized by IR, 1D-NMR ((1)H, (13)C and Distortionless Enhancement by Polarization Transfer - DEPT-135) and 2D-NMR (COSY, HSQC and HMBC) as well as mass spectroscopy analysis (HRMS). The synthesized compounds were tested for their antituberculosis activity against Mycobacterium tuberculosis H37Ra in vitro. Based on this activity, compound 4a showed the most potent inhibitory activity, with a minimum inhibitory concentration (MIC) value of 17 μM. In addition, six other synthesized compounds, 5a and 5c–5g, exhibited moderate activity, with MIC ranges between 60 μM to 140 μM. Compound 4a showed good bactericidal activity with a minimum bactericidal concentration (MBC) value of 34 μM against Mycobacterium tuberculosis H37Ra. Molecular docking studies for compound 4a on alpha-sterol demethylase was done to understand and explore ligand–receptor interactions, and to hypothesize potential refinements for the compound.